Estimation of Efficiency of Use of Dairy Products Enriched with Enter Sorbent Dietary Fibers on Immunophysiological Indicators of the Rat Organism - N. Ablaikhanova; Z. Yessimsiitova; U. Amzeyeva; A. Mukhitdinov; S. Mankibaeva; A. Zorbekova; S.N. Abdreshov; A. Kozhamzharova; A. Konysbayeva; S. Tuleukhanov (Journal of Pharmacy and Nutrition Sciences, 2020)
At all times, the problem of healthy and wholesome food has been one of the most important problems facing human society. This problem cannot be solved by simply increasing the amount of food consumed. Plant-based antioxidants are widely used for the prevention and treatment of diseases with the aim of eliminating free radicals from the body and restoring the body's antioxidant defense system. The article shows biochemical indicators that reflect the nature of changes in the early stages of the formation of response of the animal organism during toxic poisoning and the use of sour-milk products using enter sorbent dietary fiber from rice husk. With an increase in the dosage and frequency of CCl4 administration, the effect of deep poisoning and impaired lymph dynamics was obtained. Along with a decrease in the content of total protein and urea in lymph and blood plasma, an increase in ALT and AST levels in blood plasma by 2.5–3 times, as well as an increase in thymol test, were noted. Antioxidant defense mechanisms are universal in order to increase the body's vitality.